Coevolutionary analysis of the Philopteroides Mey, 2004 (Phthiraptera: Ischnocera) parasitizing bulbuls (Passeriformes: Pycnonotidae) - Ren, Mengjiao; Gustafsson, Daniel R.; Tian, Chunpo; Grossi, Alexandra A.; Liu, Zhixiao; Zou, Fasheng (Frontiers in Ecology and Evolution, 2023)
Avian head lice comprise a diverse group of distantly related genera of lice that exhibit a strongly convergent morphology. Due to their lack of free-living stages, their strong morphological adaptations to living on the host’s head, and the limited opportunities for transfer between hosts during mating or nesting, the lateral transmission of head lice between non-conspecific hosts may be presumed to be restricted. Despite this, many species of head lice are ostensibly host generalists. We here examine lice of the head louse genus Philopteroides Mey, 2004, from bulbuls (Passeriformes: Pycnonotidae). Our phylogenetic analysis indicate that several morphologically cryptic species can be found in this group, most of which appear to be host specific. However, co-phylogenetic analyses indicate that host-switching has been common in the history of these lice, and co-speciation events have been rarer than expected. Moreover, lowest-cost co-evolutionary reconstructions under a variety of event costs are indistinguishable from random. An expanded dataset with more Philopterus-complex lice was found to be evenly balanced between host-switching and co-speciation events. We discuss some different potential paths of transmission for head lice that may impact the frequent host-switched in head lice on bulbuls.